How do you measure weight? - Adamson, Heather (Mankato, Minn Capstone Press, 2011)
Simple text and color photographs describe the units and tools used to measure weight"-
Science
a gift from book africa
1 2 13 15
Keywords: Units of measurement -- Juvenile literature; Weights and measures -- Juvenile literature; Weights and measures